2014
DOI: 10.1111/psyp.12233
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sensitivity in children: Sex differences and its relationship to parameters of emotional processing

Abstract: In adults, the level of ability to perceive one's own body signals plays an important role for many concepts of emotional experience as demonstrated for emotion processing or emotion regulation. Representative data on perception of body signals and its emotional correlates in children is lacking. Therefore, the present study investigated the cardiac sensitivity of 1,350 children between 6 and 11 years of age in a heartbeat perception task. Our main findings demonstrated the distribution of cardiac sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 121 publications
(130 reference statements)
8
71
0
Order By: Relevance
“…Recent work supports this idea: Weiss et al (2014) could demonstrate that IS was positively correlated with self-regulatory capacities as assessed by questionnaire. And also Koch and Pollatos (2014) showed that IS is positively correlated with greater adaptability as assessed by questionnaire in children. It can be followed that interoception helps to preserve limited resources involved in self-regulation, presumably by faster or more differentiated detection of bodily response changes occurring in significant situations such as social rejection and might help to constitute a feeling of higher control over one’s negative experiences in everyday life.…”
Section: Discussionmentioning
confidence: 89%
“…Recent work supports this idea: Weiss et al (2014) could demonstrate that IS was positively correlated with self-regulatory capacities as assessed by questionnaire. And also Koch and Pollatos (2014) showed that IS is positively correlated with greater adaptability as assessed by questionnaire in children. It can be followed that interoception helps to preserve limited resources involved in self-regulation, presumably by faster or more differentiated detection of bodily response changes occurring in significant situations such as social rejection and might help to constitute a feeling of higher control over one’s negative experiences in everyday life.…”
Section: Discussionmentioning
confidence: 89%
“…A cause for this might be that we assessed only male participants who have higher IAc in some studies [1,68]. It might also be the case that the TMS procedure itself increased stress and sympathetic activation which then, in turn, could facilitate heartbeat rstb.royalsocietypublishing.org Phil.…”
Section: Discussionmentioning
confidence: 99%
“…Interoception has been shown to be critical for the sense of self and the creation of a subjective perspective from which the world is experienced (Varela et al, 1991;Craig, 2002Craig, , 2009Critchley et al, 2004;Berlucchi and Aglioti, 2010;Park and Tallon-Baudry, 2014). It is also important for awareness and regulation of emotions (Dunn et al, 2007;Silani et al, 2008;Herbert et al, 2011;Füstös et al, 2013;Koch and Pollatos, 2014) as well as empathy (Singer et al, 2009;Bird et al, 2010;Lamm and Singer, 2010;Terasawa et al, 2014). Furthermore, IA is critical for decision making (Sanfey et al, 2003;Dunn et al, 2010;Sütterlin et al, 2013) and self-control of behavior in various situations with impact on health and disease (Herbert et al, 2007(Herbert et al, , 2012aHerbert and Pollatos, 2014).…”
Section: Introductionmentioning
confidence: 99%